ANALISIS PARTISIPASI MASYARAKAT TERHADAP PERENCANAAN DAN PEMBANGUNAN PLTMH DI PANEKI DESA POMBEWE KECAMATAN BIROMARU KABUPATEN SIGI - Kali, Agustinus (MEKTEK, 2011)
The purpose this research first, to know the level of society participation analysis and local institutiontowards planning, developing and generator management PLTMH at Paneki of Pombewe Biromaru DistrictSigi Regency; second, to know the role of local institution in the village in order to support this program.This research is a qualitative descriptive which is supported by quantitative with using of survey method ininformation and data collecting. Sample taking is conducted with non-probability sampling by using ofcensus or surfeited sampling technique. Hypothesis test is done by using frequency distribution table andcross tabulation.The results of this research indicates that, first, participation of society towards a planning, implementation,and management PLTMH in Paneki with the low percentage because socialization process is not so well,understanding degree of society is low, the society is focus in their activity, economic condition and sense ofbelonging on existence of PLTMH in Paneki is still less. Second, the role of local institution in this village tosupport this program is very low, because there is no coordination between village government and localinstitution as the channel of inspiration of society and also the attention of local institution towards thisPLTMH is very low.